Intertextuality and Reflexivity in Joe Wright’s Atonement (2007) - Christophe Gelly (Études Britanniques Contemporaines, 2018)
The topics of intertextuality and reflexivity are deeply interdependent, in the sense that the intertextual quality of a given work of art can act as a token of a self-conscious discourse held by this work on its relation to other texts. This essay aims at presenting the various theoretical articulations between the two concepts; it also explores the specific applications of these concepts in a comparative study of Ian McEwan’s novel and Joe Wright’s film adaptation. The ethical orientation of this reflexive dimension is also presented as another common point between the two works.